2006
DOI: 10.1111/j.1469-8137.2006.01911.x
|View full text |Cite
|
Sign up to set email alerts
|

Bypassing of a polygenic Microcyclus ulei resistance in rubber tree, analyzed by QTL detection

Abstract: Research Summary• Genetic resistance components of the Hevea brasiliensis × H. benthamiana RO 38 cultivar to Microcyclus ulei disease were investigated by inoculating isolates which succeeded in partially or completely infecting genotypes of a mapping population.• Progeny of a cross between RO 38 and a susceptible cultivar was inoculated under controlled conditions with three isolates and scored for two resistance traits. Interval mapping and a nonparametric test were used to detect resistance quantitative tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 29 publications
0
23
0
4
Order By: Relevance
“…After many studies that attempted to define parameters that could give a good description of the disease (Chee et al 1985;Junqueira et al 1990) and others describing the diversity of M. ulei strains Hashim and Almeida 1987;Junqueira et al 1986;Mattos et al 2003), the first identification of the genetic factors that could confer resistance to SALB was carried out in an interspecific hybrid (H. brasiliensis × Hevea benthamiana; Lespinasse et al 2000a). Important resistance QTLs and a major resistance gene Lespinasse et al 2000a) were described, but a further study on the same material showed that this resistance has already been bypassed by some highly pathogenic M. ulei isolates (Le Guen et al 2007). Recently, a new and apparently durable resistance to SALB was identified in the H. brasiliensis cultivar MDF 180 (Le Guen et al 2008).…”
Section: Introductionmentioning
confidence: 95%
“…After many studies that attempted to define parameters that could give a good description of the disease (Chee et al 1985;Junqueira et al 1990) and others describing the diversity of M. ulei strains Hashim and Almeida 1987;Junqueira et al 1986;Mattos et al 2003), the first identification of the genetic factors that could confer resistance to SALB was carried out in an interspecific hybrid (H. brasiliensis × Hevea benthamiana; Lespinasse et al 2000a). Important resistance QTLs and a major resistance gene Lespinasse et al 2000a) were described, but a further study on the same material showed that this resistance has already been bypassed by some highly pathogenic M. ulei isolates (Le Guen et al 2007). Recently, a new and apparently durable resistance to SALB was identified in the H. brasiliensis cultivar MDF 180 (Le Guen et al 2008).…”
Section: Introductionmentioning
confidence: 95%
“…In 1934, Microcyclus ulei, the cause of South American Leaf Blight (SALB) on rubber trees, wiped-out *Corresponding author. E-mail: traud.winkelmann@zier.uni-hannover.de rubber plantations in Southeast Asia and Brazil on a large-scale (Le Guen et al, 2007). However, due to economic reasons, rubber plantations were replaced by oil palm plantations in numerous countries, especially in Malaysia, because labor costs for the laborious latex harvesting were high and the economy of these countries was shifting to an industrial base.…”
Section: Introductionmentioning
confidence: 99%
“…The rubber tree used in commercial production in South-East Asia has a very narrow genetic basis, coming essentially from a few seeds collected at one location in Brazil by Dr Henry Wickham in 1876 (Polhamus, 1962). It is very sensitive to the pathogen Microcyclus ulei, the causative agent of South American leaf blight (Le Guen et al, 2007). South American leaf blight has essentially ended large-scale Hevea rubber production in South America, and can be expected to have a similar devastating effect if it spreads to Asia (Davis, 1997).…”
Section: Natural Rubbermentioning
confidence: 99%